Forschungsinstrumente im Kontext institutioneller (schrift-)sprachlicher Bildung - Mackowiak, Katja; Beckerle, Christine; Gentrup, Sarah; Titz, Cora (Verlag Julius Klinkhardt, 2020)
This book presents a selection of survey and evaluation instruments for recording relevant facets of institutional (written) language education. The seven methods focus on different aspects of language education as well as language and reading promotion in day-care centres and schools and address different target groups (educational professionals, teachers, children). The instruments, which were developed within the framework of the initiative "Bildung durch Sprache und Schrift" (BiSS), are primarily for research purposes, but can also be used in the training and further education of educational specialists and teachers. An online appendix provides the instruments as well as all necessary materials.